SARS-CoV-2 Seropositivity and Seroconversion in Patients Undergoing Active Cancer-Directed Therapy. Issue 12 (December 2021) - Sun, Lova; Surya, Sanjna; Goodman, Noah G.; Le, Anh N.; Kelly, Gregory; Owoyemi, Olutosin; Desai, Heena; Zheng, Cathy; DeLuca, Shannon; Good, Madeline L.; Hussain, Jasmin; Jeffries, Seth D.; et al.
Abstract : PURPOSE: Multiple studies have demonstrated the negative impact of cancer care delays during the COVID-19 pandemic, and transmission mitigation techniques are imperative for continued cancer care delivery. We aimed to gauge the effectiveness of these measures at the University of Pennsylvania. METHODS: We conducted a longitudinal study of SARS-CoV-2 antibody seropositivity and seroconversion in patients presenting to infusion centers for cancer-directed therapy between May 21, 2020, and October 8, 2020. Participants completed questionnaires and had up to five serial blood collections. RESULTS: Of 124 enrolled patients, only two (1.6%) had detectable SARS-CoV-2 antibodies on initial blood draw, and no initially seronegative patients developed newly detectable antibodies on subsequent blood draw(s), corresponding to a seroconversion rate of 0% (95% CI, 0.0 TO 4.1%) over 14.8 person-years of follow up, with a median of 13 health care visits per patient. CONCLUSION: These results suggest that patients with cancer receiving in-person care at a facility with aggressive mitigation efforts have an extremely low likelihood of COVID-19 infection.